The American deists: voices of reason and dissent in the early republic - Walters, Kerry S. (University Press of Kansas, 1992)
Introduction -- I believe in one God, Creator of the universe / Benjamin Franklin -- Reason and free inquiry are the only effectual agents against errors / Thomas Jefferson -- Nature is God's revelation / Ethan Allen -- Let man study nature's laws! / Constantin François Chasseboeuf, Comte de Volney -- My own mind is my own church / Thomas Paine -- Reason, the glory of our nature / Elihu Palmer -- The reasoning power, celestial guest, the stamp upon the soul impress'd / Philip Freneau -- The temple of reason : indefense of pure religion -- Prospect, or, View of the moral world : virtue, the highest dignity of man --The theophilanthropist : the love of God and man -- Sources and permissions -- Bibliographic essay.